Odpowiedzialność karna i dyscyplinarna nauczyciela akademickiego za ten sam czyn – rozważania na temat zbiegu odpowiedzialności penalnej nauczyciela akademickiego: [Criminal and disciplinary liability of academic teachers for a single act: Considerations on the concurrence of penal liability of academic teachers] (Studia Prawnicze / The Legal Studies, 2023)
Przedmiotem artykułu jest analiza teoretycznych podstaw rozstrzygania zbiegu odpowiedzialności karnej i dyscyplinarnej nauczyciela akademickiego za ten sam czyn. Wobec braku jednoznacznego rozstrzygnięcia tej kwestii przez ustawodawcę, problemem badawczym jest pytanie o to czy wymierzenie odpowiedzialności karnej nauczycielowi akademickiemu za dany czyn, wyłącza odpowiedzialność zawodową. Rozważania przeprowadzone zostały w oparciu o systemowe uzasadnienie wprowadzenia odpowiedzialności dyscyplinarnej oraz teoretyczno-prawne koncepcje rozstrzygania jednoczynowego zbiegu odpowiedzialności penalnej. Wnioski analizy wskazują, że odpowiedzialność karna i dyscyplinarna realizują jakościowo inne cele, wobec czego zasadne jest przyjęcie tezy o ich niezależności w analizowanym obszarze. The aim of the article is to analyse the theoretical basis for resolving the concurrence of criminal and disciplinary  liability of an academic teacher for a single act. In the absence of an explicit resolution of this issue by the legislature, the research problem is whether imposing criminal liability on an academic teacher for a given act excludes disciplinary liability. The analysis was carried out based on the systemic justification for introducing disciplinary liability and the theoretical legal concepts of resolving concurrent penal liability for a single act. The conclusions indicate that criminal and disciplinary responsibility pursue qualitatively different goals; thus, it is reasonable to assume that they are independent in this area.